2000
DOI: 10.1021/bi000214t
|View full text |Cite
|
Sign up to set email alerts
|

Probing the S1/S1‘ Substrate Binding Pocket Geometry of HIV-1 Protease with Modified Aspartic Acid Analogues

Abstract: Aspartates 25 and 125, the active site residues of HIV-1 protease, participate functionally in proteolysis by what is believed to be a general acid-general base mechanism. However, the structural role that these residues may play in the formation and maintenance of the neighboring S1/S1' substrate binding pockets remains largely unstudied. Because the active site aspartic acids are essential for catalysis, alteration of these residues to any other naturally occurring amino acid by conventional site-directed mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 59 publications
1
22
0
1
Order By: Relevance
“…The cycle initiates with water activation by hydrogen-bonding interactions with the active site aspartate residues (1) (6, 7). Bell-shaped pH-rate profiles (8)(9)(10)(11)(12) have revealed an acidic pH optimum, and structural studies (13,14) suggest that the reactant-bound enzyme contains a single protonated Asp (with a di-Asp, net charge of −1) facilitating a general acid-base mechanism, which is common among many Asp proteases (7,15). Nucleophilic attack by the water generates a reversible gem-diol intermediate, (3) which has been observed structurally (16)(17)(18) and identified experimentally (19,20).…”
mentioning
confidence: 99%
“…The cycle initiates with water activation by hydrogen-bonding interactions with the active site aspartate residues (1) (6, 7). Bell-shaped pH-rate profiles (8)(9)(10)(11)(12) have revealed an acidic pH optimum, and structural studies (13,14) suggest that the reactant-bound enzyme contains a single protonated Asp (with a di-Asp, net charge of −1) facilitating a general acid-base mechanism, which is common among many Asp proteases (7,15). Nucleophilic attack by the water generates a reversible gem-diol intermediate, (3) which has been observed structurally (16)(17)(18) and identified experimentally (19,20).…”
mentioning
confidence: 99%
“…The tolerance of ribosomal translation toward α‐ N ‐methyl amino acids has been evaluated extensively . For example, Suga′s group and Green′s group independently conducted comprehensive evaluations of 19 α‐ N ‐methyl amino acids with proteinogenic side chains and found that a majority of them were compatible with translation .…”
Section: Tolerance Of Ribosomal Translation Toward Backbone‐modified mentioning
confidence: 99%
“…It was proved by mutagenesis [7] that the aspartic acids (25,125) are principally involved in maintenance of the active state of the enzyme, more than the residues Thr (26, 126) -Gly (27,127) [8,9]. Kinetic and computational studies [10][11][12] show that the viral protease presents a high mutagenesis rate, thus it is able to develop strong resistance to inhibitors [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%